Aeration Strategies and Fan Cost Comparisons for Wheat in Mid-South Production Regions - Bridges, Thomas C.; Montross, Michael D.; McNeill, Samuel G. (Applied Engineering in Agriculture, 2005)
Numerous factors influence the sizing of aeration fans for summer-harvested crops. Thirty years of weather data for Lexington, Kentucky, were analyzed and the cost of aeration was compared for two axial fans (afan1, afan2) and one centrifugal fan (cfan1). Aeration costs were defined as the sum of the following components: the cost of owning the fan, the cost of electricity for operating the fan, a cost for wheat shrinkage during aeration, and a cost for dry matter loss (DML). The fans were selected to deliver airflow rates of approximately one, two, and three times the recommended aeration rate of 0.11 m3/min/t (0.1 cfm/bu). Aeration fan investment costs ranged from $709 (afan1) to $1739 (cfan1). Aeration costs for each fan were compared for four initial grain temperatures: 21.1°C, 23.9°C, 26.7°C, and 29.4°C (70°F, 75°F, 80°F, and 85°F); four harvest dates: 1 June, 15 June, 1 July, and 15 July; and two aeration temperature windows (0 to 15°C and 0 to 17°C). Generally, the total aeration cost increased with initial grain temperature, decreased with later harvest dates, and was not significantly affected by aeration temperature window. When the total cost of aerating the wheat was considered, the results showed that the most expensive fan (cfan1) was not appreciably more costly than the least expensive (afan1). It was also found that using fans with airflow rates above the minimum recommendation were successful in reducing the amount of wheat shrinkage and dry matter loss, which should provide the producer with a larger volume of better quality grain at market.